SURFACE CAST IRON STRENGTHENING USING COMBINED LASER AND ULTRASONIC PROCESSING - O. G. Devojno; S. F. Kukin; N. V. Spiridonov; O. S. Kobjakov; E. L. Buzun (Наука и техника)
The paper provides an analysis of ultrasonic surface plastic deformation and subsequent laser thermal strengthening of gray cast iron parts in the regime of hardening from a solid state with the purpose to obtain strengthened surface layers of bigger depth and less roughness of the processed surface. Program complex ANSYS 11.0 has been used for calculation of temperature fields induced by laser exposure.  The appropriate regime of laser processing without surface fusion has been selected on the basis of the applied complex. The possibility of displacement in the bottom boundary of α–γ-transformation temperature  for СЧ20 with 900 °С up to 800 °С is confirmed due to preliminary ultrasonic surface plastic deformation of the surface that allows to expand technological opportunities of laser quenching  of gray  cast iron from a solid state.